"Common People with Common Feelings:" Pauline Kael, James Agee, and the Public Sphere of Popular Film Criticism - Charney, Leo (Cinémas, 1996)
This essay focuses on the writings of Pauline Kael and James Agee as the leading examples of the rhetoric of American popular film criticism, which the author suggests is chatacterized by three elements: the critic's effort to distance him / herself from both other critics and the entertainment industry; to emphasize the personal and subjective nature of his / her responses; and to use his / her writing as the catalyst for a public sphere of film response.